Shaggy dog and the terrible itch - Bedford, David, 1969-; Williamson, Gwyneth, 1965- (Hauppauge, N.Y. : Barron's Educational Series, 2001)
Shaggy Dog works hard to get rid of the irritating itch that plagues him, but not until someone shows him some kindness does his problem disappear.
"First published in 2001 in Great Britain by Little Tiger Press"--P. facing t.p.
School Library Journal.
2.0
K-3
Keywords: Dogs -- Fiction; Humorous stories; Dogs -- Fiction; Humorous fiction